Perceptions About Biosimilar Medicines Among Belgian Patients in the Ambulatory Care - Vandenplas, Yannick; Barbier, Liese; Simoens, Steven; Van Wilder, Philippe; Vulto, Arnold G.; Huys, Isabelle (Frontiers in Pharmacology, 2022)
Background and objectives: Biosimilar medicines have been on the European market for 15 years. Despite the extensive and positive experience with biosimilars across Europe, their uptake remains limited in Belgium. One of the possible factors limiting uptake in clinical practice is the inadequate understanding and lack of trust in biosimilars among patients. This study aimed to assess the level of knowledge and perceptions about biosimilar medicines among Belgian patients in the ambulatory care. Methods: This study consisted of online questionnaires among Belgian patients in the ambulatory care (i.e., rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, plaque psoriasis, Crohn’s disease, ulcerative colitis, diabetes mellitus type I and II). The results were collected between December 2020 and February 2021. The data were analyzed with descriptive and inferential statistics. Results: In total, 657 patients across all disease areas of interest participated in this study. Only 38% of patients had heard of biosimilars before. Of those patients, most (58%) were aware that biosimilars are as safe and effective as their reference product. The vast majority of respondents (68%) would agree with transitioning to a biosimilar if their physician prescribed it, only 3% would never agree with a transition to a biosimilar. If a physician would propose to change their current originator biological therapy with its biosimilar, nearly all patients (95%) want their physician to explain the decision and inform them. For additional information about biosimilars, Belgian patients prefer brochures or folders (41%), or available resources on the internet (35%). Physicians were indicated as the preferred source of information (95%), followed by pharmacists (51%), academia (39%), and patient associations (35%). Most patients require information regarding the safety and efficacy (78%), price and reimbursement (64%), and the clinical development process (56%) of the biosimilar. Conclusion: Belgian patients require information about biosimilar medicines. However, most patients are open and positive towards transitioning their current biological therapy with its biosimilar if sufficiently supported by their healthcare providers.